Unraveling environmental disasters - Vallero, Daniel A.; Letcher, T. M. (Trevor M.) (Elsevier, 2023)
Unraveling Environmental Disasters, Second Edition provides scientific explanations of the most threatening current and future environmental disasters, including an analysis of ways disasters could have been prevented and how to minimize risk of similar disasters in the future. In this new edition the authors provide foundational knowledge on why certain environmental disasters occur and ways of reducing the risk of recurrences. Anyone involved in teaching or working in the main sciences of physics, chemistry, and biology, or in the applied sciences, including engineering, design, planning, and homeland security, should read the book to become acquainted with these very important issues.